2012
DOI: 10.2147/jmdh.s35493
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the implementation process and outcomes of newly introduced assistant roles: a qualitative study to examine the utility of the Calderdale Framework as an appraisal tool

Abstract: Video abstract Video

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The finding that the SPTA model required extra indirect time from the SLP is in contrast to literature which suggests that the use of allied health assistants is to allow health professionals more "free time" (Lizarondo, et al, 2010;Nancarrow, Moran, Wiseman, Pighills, & Murphy, 2012). Even so, Nancarrow et al, (2012) assert that an important component of introducing assistant roles is the decision making surrounding task delegation, which can be a complex and multi-faceted process.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The finding that the SPTA model required extra indirect time from the SLP is in contrast to literature which suggests that the use of allied health assistants is to allow health professionals more "free time" (Lizarondo, et al, 2010;Nancarrow, Moran, Wiseman, Pighills, & Murphy, 2012). Even so, Nancarrow et al, (2012) assert that an important component of introducing assistant roles is the decision making surrounding task delegation, which can be a complex and multi-faceted process.…”
Section: Discussionmentioning
confidence: 91%
“…Even so, Nancarrow et al, (2012) assert that an important component of introducing assistant roles is the decision making surrounding task delegation, which can be a complex and multi-faceted process. Further consideration of the type of treatment tasks being delegated to the SPTA in the intensive treatment of aphasia is therefore needed to maximise the cost efficiency of the role.…”
Section: Discussionmentioning
confidence: 99%
“…, Nancarrow et al . ). However, there is a risk that providing the majority of training ‘in house’ and relying on multidisciplinary working to impart knowledge and skills may restrict the extent of skills and knowledge transfer.…”
Section: Discussionmentioning
confidence: 97%
“…The impact of assistant roles in CBRS includes improved service capacity and efficiency (Hart et al 2005, Stanmore et al 2005, Moran et al 2012b, Nancarrow et al 2013, increased staff satisfaction with assistant roles (Anderson 1997, Saunders 1998, Daykin & Clarke 2000, Lindsay 2004, Cattrell et al 2005, Mackey & Nancarrow 2005, McCartney et al 2005, Moran et al 2012b, client satisfaction (Brown et al 2000, Hek et al 2004, Mackey & Nancarrow 2004, Hart et al 2005, Stanmore et al 2005 and job satisfaction of assistants (Mackey & Nancarrow 2004, Moran et al 2012c. One study found that better client outcomes were associated with a higher proportion of treatment by assistants in CBRS, although associated with increased service costs (Nancarrow et al 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, changing a health professional role refers to a complex process involving interdependent changes occurring within a variety of systems (Hatem-Asmar, 1997;Laurant et al, 2010;Nancarrow, Moran, Wiseman, Pighills, & Murphy, 2012). For instance, professional education has to be enhanced and training programs have to be reviewed.…”
Section: Introductionmentioning
confidence: 99%